The Potential of Bean Extract (Phaseolus vulgaris) Based on Haemagglutination - Muhammad Zelizar Yarta; Jessy Gre dini Kurnia; Shafiy Dwi Febrianto; Treticha Kaa Leramau; Cityta Putri Kwarta (Biology, Medicine, & Natural Product Chemistry, 2026)
Blood typing is a crucial procedure in healthcare,but dependence on expensive an difficult-to-acces imported reagents is a constraint, especially in 3T (underdeveloped, frontier, and othermost) areas. This study aimed to evaluate the potential of bean seed extract (Phaseolus vulgaris), as a local natural resource, to be used as an alternative reagent candidate in ABO blood group screening through in vitro haemagglutination testing. The research method involved several stages, namely the extractionof lectin from bean seed using a 0.9% physiological NaCl solution, the preparation of a 5% erythrocytre suspention form donors with blood group A, B, AB, and O and microscope agglutination tests at various extract ratios and dilution titres. Validation was performed by comparing the agglutination results with commercial anti-A and anti-B reagents. Data were analysed qualitatively descriptively and quantitatively using the Kruskal-Wallis and Dunn nonparametric tests. The results showed that the bean lectin extract successfully agglutinated blood group A, B, and AB erythrocytes specifically, while showing no reaction to blood group O. The strongest and most stable agglutination reaction was observed at a mixture ratio of extract and NaCl of 2:4 and 2:6. Statistical analysis showed a significant difference in agglutination scores between blood group O and blood groups A, B, and AB (p < 0.05), which confirms the specificity of the lectin reaction. The validation test also showed agglutination patterns consistent with commercial reagents. In conclusion, broad bean seed extract has great potential to be developed as an economical, easily accessible, and effective natural agglutination reagent for ABO blood group screening, thus providing an innovative solution to overcome the limitations of conventional reagents in healthcare facilities.